Analisis Tingkat Kesehatan KSPPS BMT Bina Ummat Mandiri Kota Tegal Tahun 2016 - Teguh Hardi Raharjo; Heny Indriani (JBIMA (Jurnal Bisnis dan Manajemen), 2017)
This research aims to assess the soundness level of KSPPS BMT BUM Tegal in 2016 based on the Regulations of Deputy for Supervision of the Ministry of Coorporative and SME No. 07/PerDep.6/IV/2016. The subject of this research is KSPPS BMT BUM Tegal and the object itself is the soundness level of KSPPS BMT BUM Tegal. The data analysis technique used in this research is descriptive analysis. In this research, the data were collected through documentation and interview methodes. The result shows that the soundness level of KSPPS BMT BUM Tegal in 2016 was in moderately soundness category with a mean score of 75,45 with the details as follows: (1) the capital aspect attained a mean score of 5,50 and was in the under surveillance category; (2) the quality of productive assets aspect attained a mean score of 14,45 and was in the moderately soundness category; (3) the management aspect attained a mean score of 11,50 and was in soundness category; (4) the efficiency aspect attained 6,50 and was in the under surveillance category; (5) the liquidity aspect attained a mean score of 12,50 and was in soundness category; (6) the identity cooperative attained a mean score of 10,00 and was in soundness category; (7) the autonomy and growth aspects attained a mean score of 5,00 and was in under special surveillance; and (8) the sharia principal persuance aspect attained a mean score of 10,00 and was in soundness category.